Nurses Burnout, Resilience, and Its Association With Socio-Demographic Factors During COVID-19 Pandemic - Jamebozorgi, Majid Heidari; Karamoozian, Ali; Bardsiri, Tayebe Ilaghinezhad; Sheikhbardsiri, Hojjat (Frontiers in Psychiatry, 2022)
Introduction: During COVID-19 pandemic, nurses have had high workload and have been exposed to burnout. Personality characteristics, such as resilience, are a buffer against stressful events and work-related psychological problems such as burnout. Given the important role of nurses in the healthcare system, this study investigated the relationship between resiliency and burnout in nurses. Methods: This cross-sectional descriptive-analytical study was carried out in April–June 2021 on 364 nurses working in two hospital in Iran. The subjects were chosen by census sampling. The instruments were Maslach burnout inventory (MBI), Connor-Davidson Resiliency Scale (CDRISC) and a demographic check-list. Data were analyzed by SPSS-22. Data analysis was done through the Shapiro-Wilk, Kruskal–Wallis test, Mann–Whitney U test, correlation analysis, and generalized linear model. Results: Overall, the findings showed that nurses experienced severe burnout symptoms and a moderate level of resilience. The two metrics of burnout, emotional exhaustion and personal accomplishment had a significantly negative correlation with resilience (r =-0.442, p < 0.001 and r = -0.351, p = 0.03, respectively). Linear regression analysis showed that demographic characteristics (Hospital type, ward type, gender and, overtime) were the main predictors of the three metrics of burnout. A significant negative correlation was identified between burnout and resilience highlighting the role of resilience in alleviating burnout during this pandemic. (P< 0.05) Conclusion: Findings suggest national and local policies in Iran to need providing Psychological support and workshops to increase the resiliency-related skills of the nurses about stress management strategies to help them reduce job burnout.